What Happens When Enclaves Fail to Support Transnational Diaspora Entrepreneurship? - Osaghae, Osa-Godwin; Cooney, Thomas M. (Senate Hall, 2021)
In the literature examining enclave activities, the focus is usually on immigrant marginalisation or segregation, and on the opportunity that an enclave provides for local immigrant economic activity. However, there is a dearth of literature discussing the possible consequences when an enclave fails to support Transnational Diaspora Entrepreneurship (TDE) activity. Addressing this gap in the literature, this study employs a comparative narrative analysis of immigrant enclaves, TDE frameworks and a primary dataset. Based on semi-structured interviews with 11 Nigerian transnational diaspora entrepreneurs in the Blanchardstown area of Dublin who travel between Ireland and Nigeria for transnational entrepreneurial activity, the study suggests that the failure of immigrant enclaves to provide a localised Country of Origin (COO) environment, infrastructures and resources will decrease TDE activity. The article contributes to literature on diaspora entrepreneurship by suggesting that the undertaking of TDE is dependent on the level of COO cultural elements within the enclave and that a reduction in enclave cultural elements will diminish TDE activity.
Keywords: immigrant-enclave|Transnational Diaspora Entrepreneurship|entrepreneurial opportunity|environment|infrastructures|resources